Investigation of Mechanical Numerical Simulation and Expansion Experiment of Expandable Liner Hanger in Oil and Gas Completion - Yong Chen; Guo Ping Xiao; Wen Jian Zhong; Hao Yi (Shock and Vibration)
The expansion experiment of the expansion liner hanger is a one-time failure process, so in order to save cost, the finite element technology needs to be used to simulate the expansion experiment. Obtaining the mechanical parameters of the expansion liner hanger can effectively optimize the size of the expansion liner hanger structure and guide the expansion completion. Firstly, main structure and principle of expandable liner hanger were introduced. Secondly, mechanical equilibrium equations of the expandable process were established to obtain pressure of the expandable fluid, and pressure of the expandable fluid is obtained. Thirdly, finite element (FE) simulation mechanical model of the expansion of the Ø244.5 mm × Ø177.8 mm expandable liner hanger was established to analyze the hang mechanism and the change rule of mechanical parameters during the expansion. The FE results have shown that radial displacement and residual stress of the inner wall of hanger varied in 5 cycles, and the expansion ratio of the expandable tube was 7.4% during the expansion. The expansion force did not change stably but gradually increased in stages. And the hydraulic pressure required for the expandable cone to continuously move down was 18 MPa. According to the contact stress generated on five rubber cylinders and the contact stress generated on five metal collars, the total hang force has been calculated, which exceeds 1000 kN and meets the design requirements. Lastly, the expansion test results have shown that expansion pressure was 19 MPa, and the expansion rate was 7.1%. The mechanical analysis results of the expandable liner hanger were in good agreement with the experiment results in this study, which provide important mechanical parameters for well completion with expandable liner hanger.